Integration of resilience and sustainability: from theory to application. Issue 3 (14th September 2015) - Achour, Nebil; Pantzartzis, Efthimia; Pascale, Federica; Price, Andrew D. F.
Abstract : Purpose: – This study aims to explore the challenges associated with the integration of resilience and sustainability, and propose a workable solution that ensures resilient and sustainable buildings. Recent research outcomes suggest that the number of natural hazards, both environmental and geophysical, will increase due to the effect of global warming. Various approaches have been investigated to reduce environmental degradation and to improve the physical resilience to natural hazards. However, most of these approaches are fragmented and when combined with cultural barriers, they often result into less-efficient assessment tools. Design/methodology/approach: – The primary source of information used to develop this paper has been research publications, policy papers, reports and tool guidelines. A set of questions were developed to guide the review which was complemented with information distilled from the HFA 2005-2015 to develop an integration process to evaluate 10 international sustainability appraisal tools. Findings: – The major finding of this research is that, from a technical point of view, resilience and sustainability could be integrated. However, it requires a long and thorough process with a multidisciplinary stakeholder team including technical, strategic, social and political parties. A combination of incentives and policies would support this process and help people work towards the integration. The Japanese model demonstrates a successful case in engaging stakeholders in the process which led to the development of a comprehensive appraisal tool, CASBEE®, where resilience and sustainability are integrated. Practical implications: – Although data have been sought through literature review (i.e. secondary data), the research is expected to have significant impact, as it provides a clear theoretical foundation and methods for those wishing to integrate resilience within current sustainability appraisal tools or develop new tools. Social implications: – This paper provides original concepts that are required to reduce fragmentation in the way resilience and sustainability are addressed. It sets up a new research agenda which has the potential to have a strong impact due the fact that sustainability and resilience are getting higher on the political priority scale. Originality/value: – This paper provides findings of an original idea to reduce fragmentation in the way resilience and sustainability are addressed. It sets up a new research agenda which has the potential to have a strong impact due the fact that sustainability and resilience are getting higher on the political priority scale.